Renal Tumors in Young Adults: A Single-Center Experience From a Developing Country - Mohsin, Rehan; Hashmi, Altaf; Sultan, Gohar; Shehzad, Asad; Mubarak, Muhammed; Ghazanfar, Nazish; Tunio, Mutahir Ali; Naqvi, Syed Ali Anwer; Rizvi, Syed Adeeb ul Hassan (Urology Journal, 2012)
Purpose: To determine the pattern and outcome of renal tumors in young adults in a large surgical series in Pakistan. Materials and Methods: We retrospectively analyzed 133 young adults (age: ≥ 16 to ≤ 40 years) with 136 renal tumors, who underwent surgical treatment for suspected renal cancer from 1994 till 2010. The clinical and pathological parameters were determined and their impact on final outcome was analyzed. Results: The mean age of the patients was 33.3 ± 6.2 years. Of 136, 121 (88.9%) renal tumors were malignant and 15 (11%) were benign. Among malignancies, 76 (62.7%) patients had stage I or II tumors, 22 (18.1%) stage III, and 23 (19%) stage IV at surgery. The overall cancer-specific survival for malignant tumors at 1, 5, and 10 years was 97%, 83%, and 83%, whereas the cancer-free survival (CFS) was 80%, 63%, and 37%, respectively. Patients with age ≤ 35 years had 1 and 5-year CFS of 83% and 71%, respectively, as compared with 76% and 49% for patients > 35 years (P = .02; odds ratio = 2.3; P = .03). Regarding tumor size, 1 and 5-year CFS for tumors ≤ 10 cm was 93% and 75%, while tumors > 10 cm showed CFS of 56% and 41%, respectively (P = .0001; odds ratio = 4.2; P = .0001). For stage I tumors, CFS at 1 and 5 years was 98% and 84%; for stage II, 82% and 63%; and for stage III, 62% and 50%, respectively. One-year survival for stage IV was 48% only (P = .0001). Conclusion: A wide heterogeneity of renal tumors is seen in young adults with delayed presentation.